Transformational and transactional leadership styles in enhancing nurse educator’s job satisfaction: An integrative analysis - Moey, Soo Foon; Abdulahi Hashi, Abdurezak (2016)
The challenges confronting Malaysia’s nursing training colleges in their futuristic movement towards world class institutions were enormous. Among such challenges were job satisfaction and retention of nurse educators. As nursing education increased its’ complexity, leadership styles employed in these nursing training institutions played a crucial role in achieving nurse educators’ job satisfaction. This paper examined the influence of transformational and transactional leadership style employed by nursing academic leaders on nurse educator’s job satisfaction. This research employed a qualitative method together with documents and observations. Purposive sampling was undertaken in selecting nine nurse educators from three nursing colleges from Johor and Melaka. Data from the interview were then summarized in answering nurse educators' job satisfaction and perceived leadership styles and practices of nursing academic leaders. The responses from the verbatim transcriptions were analysed using the software Atlas Ti. The strong relationship between nursing academic leadership styles and nurse educators’ job satisfaction suggested that the academic nursing transformational leadership style played a prominent role on subordinates’ job satisfaction and that nursing academic leaders’ transformational leadership practices and attributes had the ability to encourage subordinates to achieve more than what they planned. Transactional leadership practised by the nursing academic leaders indicated a very weak link to subordinates job satisfaction as the leaders’ emphasis on payoffs for performance and corrective actions were not as acceptable to that transformational leadership attributes practised by the leaders. The study uncovered effective leadership was enacted via engaging leadership where the engaging leader enabled the development of an organization modelled by a culture of integrity,